Monitoring of Respiratory Muscle Function in Critically Ill Children. Issue 5 (May 2020) - Mortamet, Guillaume; Crulli, Benjamin; Fauroux, Brigitte; Emeriaud, Guillaume
Abstract : Objectives: This review discusses the different techniques used at the bedside to assess respiratory muscle function in critically ill children and their clinical applications. Data Sources: A scoping review of the medical literature on respiratory muscle function assessment in critically ill children was conducted using the PubMed search engine. Study Selection: We included all scientific, peer-reviewed studies about respiratory muscle function assessment in critically ill children, as well as some key adult studies. Data Extraction: Data extracted included findings or comments about techniques used to assess respiratory muscle function. Data Synthesis: Various promising physiologic techniques are available to assess respiratory muscle function at the bedside of critically ill children throughout the disease process. During the acute phase, this assessment allows a better understanding of the pathophysiological mechanisms of the disease and an optimization of the ventilatory support to increase its effectiveness and limit its potential complications. During the weaning process, these physiologic techniques may help predict extubation success and therefore optimize ventilator weaning. Conclusions: Physiologic techniques are useful to precisely assess respiratory muscle function and to individualize and optimize the management of mechanical ventilation in children. Among all the available techniques, the measurements of esophageal pressure and electrical activity of the diaphragm appear particularly helpful in the era of individualized ventilatory management. Abstract : Supplemental Digital Content is available in the text.